2008
DOI: 10.1186/1471-2105-9-363
|View full text |Cite
|
Sign up to set email alerts
|

Virtual screening of GPCRs: An in silico chemogenomics approach

Abstract: Background: The G-protein coupled receptor (GPCR) superfamily is currently the largest class of therapeutic targets. In silico prediction of interactions between GPCRs and small molecules in the transmembrane ligand-binding site is therefore a crucial step in the drug discovery process, which remains a daunting task due to the difficulty to characterize the 3D structure of most GPCRs, and to the limited amount of known ligands for some members of the superfamily. Chemogenomics, which attempts to characterize i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 73 publications
3
107
2
Order By: Relevance
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 90%
“…The results reported here are comparable to those from other similar works [19][20][21][22] which showed that GPCR modeling [23][24][25][26][27][28][29][30][31] in the absence of a crystal structure can be a valid replacement [32][33][34][35][36][37][38][39] for structural and functional exploration of GPCR receptors, and for the discovery [21,[40][41][42][43], VS [44][45][46][47][48][49][50][51][52] and optimisation [23,53] of their ligands.…”
Section: Introductionsupporting
confidence: 90%
“…The goal is to be able to use the known protein-chemical interactions for a given protein family to help predict which chemicals the proteins of another protein family will interact with, for which no interaction information is known. We obtained a data set from Jacob et al [22] which includes all chemicals and their G protein-coupled receptor (GPCR) targets, built from an exhaustive search of the GPCR ligand database GLIDA [27]. The data set contains 80 GPCR proteins across 5 protein families, 2687 compounds, and a total of 4051 protein-chemical interactions.…”
Section: Protein-chemical Interaction (Data Sets 13 -24)mentioning
confidence: 99%
“…CPI-specific kernel methods based on the kernel trick were recently formulated by Jacob, Vert, and co-workers. [33,34] The result of their work that is important to discussion here is that they showed for CPIs (c 1 , p 1 ) and (c 2 , p 2 ),…”
Section: Cpi Similarity Metrics and Examplesmentioning
confidence: 88%